Students’ Generated Animation: An Innovative Approach to Inculcate Collaborative Problem Solving (CPS) Skills in Learning Physics - Norazlilah Md Nordin; Kamisah Osman (Journal of Education in Science, Environment and Health)
Inculcating collaborative problem solving (hereinafter CPS) skills to help develop students' knowledge, especially for problem solving (PS) involved in the subject of physics is of utmost importance in the 21st century. It was on such grounds that in the present study, physics PS learning was innovated by engaging students’ generated animation within the recent CPS learning framework process. Next, the effectiveness of the steps in this innovative approach, which was developed as Lensmation CPS Module, in inculcating CPS skills was determined. Seventy respondents were involved in this quasi-experimental study, in which one treatment group was exposed to the module whereas the control group practised the conventional PS learning. In the course of completing their PS tasks, the students who were involved in this study had their CPS skills assessed using the CPS Proficiency Rubrics. MANOVA analysis revealed significant effects on CPS skills between the two groups. It is concluded that the innovative PS learning approach which tapped into students’ ICT literacy in physics CPS learning was effective in inculcating CPS skills among the students.